2005
DOI: 10.1002/pmic.200401079
|View full text |Cite
|
Sign up to set email alerts
|

A rare and often unrecognized cerebromeningitis and hemodynamic disorder: A major cause of sudden death in somatic cell cloned piglets

Abstract: In this study, we generated 40 somatic cell cloned (scNT) piglets. Of these, five piglets were stillborn, 22 scNT piglets died suddenly within the first week of life, and 1 piglet died after 40 days. Twelve scNT piglets are still healthy. The birth weights of compromised scNT piglets in comparison with those of normal scNT piglets are significantly reduced (0.80 +/- 0.29 vs 1.27 +/- 0.30 kg, p < 0.05), in spite of longer gestation (114 versus 120 day). Significant findings from histological examinations showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 30 publications
2
54
0
Order By: Relevance
“…An important advancement was made in the field recently when several research groups succeeded in cloning piglets from somatic cells (Betthauser et al, 2000;Onishi et al, 2000;Polejaeva et al, 2000;Bondioli et al, 2001;Yin et al, 2002Yin et al, , 2003Park et al, 2004Park et al, , 2005. This finding has permitted the genetic improvement of farmed pigs and the production of transgenic pigs for medical use and organ transplantation .…”
Section: Introductionmentioning
confidence: 99%
“…An important advancement was made in the field recently when several research groups succeeded in cloning piglets from somatic cells (Betthauser et al, 2000;Onishi et al, 2000;Polejaeva et al, 2000;Bondioli et al, 2001;Yin et al, 2002Yin et al, , 2003Park et al, 2004Park et al, , 2005. This finding has permitted the genetic improvement of farmed pigs and the production of transgenic pigs for medical use and organ transplantation .…”
Section: Introductionmentioning
confidence: 99%
“…Cloning of pigs has been performed previously primarily by somatic cell nuclear transfer but this method often results in low numbers of cloned animals due to loss of embryos either during the gestation period or death of the piglets shortly after birth. 2,3 It has been suggested that cloning gives rise to altered metabolic characteristics, 4 skin abnormalities 5,6 and other physiological defects which may limit the use of cloned animals as experimental models. However so far there is only one study that has explored the gut microbiota in obese cloned pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Cloning by somatic cell nuclear transfer (SCNT) in pigs remains a lowefficiency process with a small proportion of live clones and increased mortality perinatally (Park et al, 2005;Whitworth et al, 2009). The increased mortality has been attributed to a range of causes, including metabolic and cardiopulmonary abnormalities (Hill et al, 1999;Wells et al, 1999), lymphoid hypoplasia (Renard et al, 1999), and neonatal respiratory distress (Hill et al, 1999).…”
Section: Introductionmentioning
confidence: 99%